Gait selection for quadruped and hexapod walking systems - Silva, Manuel F. (2004)
This paper studies periodic gaits of quadruped and hexapod locomotion systems. The purpose is to determine the best set of gait and locomotion variables for different robot velocities based on the system dynamics during walking. In this perspective, several performance measures are formulated and a set of experiments that reveal the influence of the gait and locomotion variables upon those proposed indices are performed.